2022
DOI: 10.3389/fonc.2022.893877
|View full text |Cite
|
Sign up to set email alerts
|

The values of systemic immune-inflammation index and neutrophil-lymphocyte ratio in predicting testicular germ cell tumors: A retrospective clinical study

Abstract: The values of systemic immuneinflammation index and neutrophillymphocyte ratio in predicting testicular germ cell tumors: A retrospective clinical study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Several studies have shown that many types of malignant neoplasms play an important role in the carcinogenic process and survival with respect to systemic inflammation [6][7][8][9][10][11][12][13][14][15][16]24]. Tumor cells themselves release cytokines and chemokines, which are thought to circulate and induce a systemic inflammatory response [25], resulting in changes in neutrophils, lymphocytes, and platelets [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that many types of malignant neoplasms play an important role in the carcinogenic process and survival with respect to systemic inflammation [6][7][8][9][10][11][12][13][14][15][16]24]. Tumor cells themselves release cytokines and chemokines, which are thought to circulate and induce a systemic inflammatory response [25], resulting in changes in neutrophils, lymphocytes, and platelets [26].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation-related parameters such as NLR, PLR, and SII have been focused on as potential useful markers for the assessment of systemic inflammation, and previous studies have suggested that these biomarkers may be one of the prognostic predictive parameters for PCa [12,26,31]. In a study of 291 patients with pathologically confirmed localized PCa who underwent RP, 114 (39.2%) developed BCR within a median follow-up of 48 months [12]. The incidence of BCR was significantly higher in the high NLR group (50.7%) and the high SII group (48.77%) than in the low NLR and SII groups [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The haematological markers include the neutrophil–lymphocyte ratio (NLR) [ 8 ], the platelet–lymphocyte ratio (PLR) [ 9 ], the modified Glasgow prognostic score (mGPS) [ 10 ], as well as the systemic inflammation index (SII) [ 11 ]. Computational equation for SII is: SII = platelet × neutrophil/lymphocyte [ 12 ]. SII is presented as a combination of NLR and PLR.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, new biomarkers with further proper prognostic stratification in germ cell populations are still needed. Programmed death ligand-1 status as well as neutrophil–lymphocyte ratio or systemic inflammatory index were evaluated as prognostic biomarkers in several studies ( 7 , 8 ), with favorable results as independent predictors of outcome in a selected population of germ cell tumors, but their usefulness in practice has not been established. Thus, understanding disease better with more precise identification of patients with an adverse prognosis is crucial to improving patient management, as might be disease monitoring.…”
Section: Introductionmentioning
confidence: 99%